Changes in creatinine‐to‐cystatin C ratio over 4 years, risk of diabetes, and cardiometabolic control: The China Health and Retirement Longitudinal Study. Issue 12 (10th August 2021) - Qiu, Shanhu; Cai, Xue; Yuan, Yang; Xie, Bo; Sun, Zilin; Wu, Tongzhi
Abstract: Background: Creatinine‐to‐cystatin C ratio has attracted substantial interest as a measure to reflect health well‐being, but no studies have assessed whether its longitudinal changes are associated with risk of diabetes. We aimed to examine their association, along with the exploration of the relationship of such changes with cardiometabolic control in middle‐aged and older adults. Methods: We included a total of 3278 participants aged ≥45 years who provided measurements of creatinine and cystatin C at baseline and 4 years later from the China Health and Retirement Longitudinal Study. Diabetes was diagnosed based on glucose, hemoglobin A1c (HbA1c), medical history, or use of antidiabetic mediations. Odds ratio (OR) and 95% confidence interval (CI) were obtained using logistic regression analyses. Results: After 4‐year follow‐up, 272 participants developed diabetes. Larger increases in creatinine‐to‐cystatin C ratio were associated with lower risk of diabetes. The multivariable‐adjusted OR for diabetes per 1 SD increase in creatinine‐to‐cystatin C ratio was 0.84 (95% CI 0.72‐0.98). Compared with participants showing decreases in creatinine‐to‐cystatin C ratio but increases in body mass index (BMI), those experiencing increases in creatinine‐to‐cystatin C ratio and decreases in BMI had the largest risk reduction (multivariable‐adjusted OR 0.52). Changes in creatinine‐to‐cystatin C ratio showed inverse correlation with blood pressure, HbA1c, lipids, and C‐reactive protein at the 4‐year follow‐up. Moreover, they also correlated inversely with changes in HbA1c and C‐reactive protein (all P  ≤ 0.004). Conclusions: Increases in creatinine‐to‐cystatin C ratio led to reduced risk of diabetes and may benefit cardiometabolic control. Abstract : Highlights Increases in creatinine‐to‐cystatin C ratio over 4‐year were associated with lower risk of diabetes in middle‐aged and older adults. Increases in creatinine‐to‐cystatin C ratio were associated with a favorable cardiometabolic profile at the 4‐year follow‐up. Increases in creatinine‐to‐cystatin C ratio may benefit cardiometabolic control by improving glycemic control and lowering the degree of inflammation. 摘要: 背景: 肌酐与胱抑素C比值作为反映健康状况的一种指标获得了广泛关注, 但没有研究评估其纵向变化是否与糖尿病风险相关。本研究旨在评估两者之间的关联, 并探索肌酐与胱抑素C比值的变化与中老年人心脏代谢控制的关系。 方法: 我们共纳入了3278名来自中国健康与养老追踪调查中年龄≥45岁且提供了基线和4年后肌酐和胱抑素C测量值的参与者。糖尿病的诊断标准主要依据葡萄糖、糖化血红蛋白A1c(HbA1c)、病史或抗糖尿病药物的使用。优势比(OR)和95%置信区间(CI)使用logistic回归分析获得。 结果: 经过4年的随访, 272名参与者罹患糖尿病。肌酐与胱抑素C比值增加越多, 糖尿病风险越低。肌酐与胱抑素C比值每增加1个标准差, 经多变量校正的糖尿病OR值为 0.84(95% CI 0.72‐0.98)。与肌酐与胱抑素C比值降低但体重指数(BMI)增加的参与者相比, 那些肌酐与胱抑素C比值增加和BMI降低的参与者糖尿病风险降低最大(多变量调整后的OR为0.52)。在4年随访中, 肌酐与胱抑素C比值的变化与血压、HbA1c、血脂和 C反应蛋白呈负相关。此外, 它们还与HbA1c和C反应蛋白的变化呈负相关(所有 P ≤ 0.004)。 结论: 肌酐与胱抑素C比值的增加可使得糖尿病风险降低, 并可能有益于心脏代谢控制。